School of the Future – the Ideas Underlying the Swedish National Reform of Upper-Secondary Education 2011 - Zineldin, Mosad; Boren, Peter (Educological discourse, 2014)
In the article reveals an idea of the school of the future, describe different aspects of the Swedish New Reform. Special attention is paid to the description of the 5Qs Model which incorporates essential and multidimensional attributes, missing in other models.